Parietal lesion effects on cued recall following pair associate learning. (July 2015) - Ben-Zvi, Shir; Soroker, Nachum; Levy, Daniel A.
Abstract: We investigated the involvement of the posterior parietal cortex in episodic memory in a lesion-effects study of cued recall following pair-associate learning. Groups of patients who had experienced first-incident stroke, generally in middle cerebral artery territory, and exhibited damage that included lateral posterior parietal regions, were tested within an early post-stroke time window. In three experiments, patients and matched healthy comparison groups executed repeated study and cued recall test blocks of pairs of words (Experiment 1), pairs of object pictures (Experiment 2), or pairs of object pictures and environmental sounds (Experiment 3). Patients' brain CT scans were subjected to quantitative analysis of lesion volumes. Behavioral and lesion data were used to compute correlations between area lesion extent and memory deficits, and to conduct voxel-based lesion-symptom mapping. These analyses implicated lateral ventral parietal cortex, especially the angular gyrus, in cued recall deficits, most pronouncedly in the cross-modal picture–sound pairs task, though significant parietal lesion effects were also found in the unimodal word pairs and picture pairs tasks. In contrast to an earlier study in which comparable parietal lesions did not cause deficits in item recognition, these results indicate that lateral posterior parietal areas make a substantive contribution to demanding forms of recollective retrieval as represented by cued recall, especially for complex associative representations. Highlights: Investigated recollective role of ventral parietal cortex. Lesion-effects study of cued recall following pair-associate learning. Checked recall of word pairs, picture pairs, picture–sound pairs. Area lesion extent–performance correlations and VLSM identified relevant areas. Angular gyrus implicated in cued recall deficits, especially in cross-modal task.